Differential risk signals of cutaneous adverse drug reactions among β-lactam antibiotics: ceftriaxone shows increased signals for SJS/TEN in clinical and real-world cohorts - Leonard von Grundherr; Henrike Alexandra Faesser; Andreas Recke; Ralf J. Ludwig; Katharina Boch; Philip Curman (Frontiers in Medicine, 2026)
Background Cutaneous adverse drug reactions (CADRs) are triggered by numerous antibiotic drugs. Most drug reactions are in the spectrum of a maculopapular eruption (MPE) with a self-limiting disease course. In contrast, severe cutaneous adverse reactions (SCARs), including Stevens–Johnson syndrome/toxic epidermal necrolysis (SJS/TEN), are rare but may follow a life-threatening course. In this study, we investigated the key drug-related triggers of CADRs in a retrospective single-center cohort and, based on these findings, evaluated the differential risk of the implicated agents using large-scale real-world data. Methods Data from 122 patients diagnosed with CADRs, including 5 with confirmed SJS/TEN treated at a tertiary-referral hospital were retrospectively analyzed in a descriptivesingle-center cohort study. To further explore our findings, we performed a large-scale real-world cohort study using TriNetX to assess the occurrence of SJS/TEN following exposure to selected drugs. Separate analyses were conducted comparing ceftriaxone with aminopenicillins, cefazolin, cefuroxime, and allopurinol, which was included as a positive control. Odds ratios were calculated after running propensity-score-matching for demographic characteristics and SJS/TEN-risk factors. Results In the single-center cohort, MPE was the predominant phenotype among CADRs attributed to aminopenicillins and first- and second-generation cephalosporins. In contrast, among CADRs attributed to third-generation cephalosporins, represented by ceftriaxone in this single-center cohort, SCARs were the predominant reaction type, with ceftriaxone accounting for 40% of SJS/TEN cases. These findings were underlined by the real-world cohort analysis, in which aminopenicillins and early-generation cephalosporins showed significantly lower odds of SJS/TEN than ceftriaxone (0.389 (95% CI 0.291–0.520) for aminopenicillins; 0.392 (0.290–0.529) for cefazolin; 0.300 (0.157–0.572) for cefuroxime). Conclusions While both datasets need to be interpreted within the context of their respective limitations, our analysis, are in line with previous studies, suggesting that ceftriaxone may have an SJS/TEN risk profile that exceeds the class-wide risk observed among cephalosporins. This underscores the importance of substance-specific, rather than purely class-based approaches in both clinical research and pharmacovigilance.